Cooperative Play Affects Social Interaction of Children Who Have Introvert Personality - Ira Rahmawati; Ah. Yusuf; Ilya Krisnana (Jurnal Ners, 2010)
Introduction: One of school age children may developing task is learning to interact with their peer groups. The introvert have problem with their social interaction. One ways that can increase the social skill is play activities with social situation. So social play activities: cooperative play can be one of alternative solution to increase social interaction of children with introvert symptom. This study was aimed to explain effect of social play activities: cooperative play on social interaction of children with introvert symptom.Methods: Quasy experiment design was used in this study. The population was school aged children with introvert symptom in SDN Kendangsari III/278 Surabaya. Total sample was 23 respondents consist of 12 respondents as treatment group and 11 respondents as controlled group. The independent variable was social play activities: cooperative play. The dependent was social interaction of children with introvert symptom. The Data was analyzed by Wilcoxon Signed Rank Test and Mann Whitney U Test with level significance ofα ≤ 0.005.Result: Result showed that social play activities: cooperative play had significant effect on social interaction of children with introvert symptom (increased). Wilcoxon Signed Rank Test showed treatment group had p = 0.002 and controlled group had p = 1.00. Mann Whitney U Test showed p = 0.002.Conclusion:  It concluded that social play activities: cooperative play can be one way to change social interaction of children with introvert symptom. Further studies should involve larger respondents and better measurement tools to obtain more accurate results.